Affects and Interstices. David Vilaseca and the Erratic Autobiography (Anclajes, 2024)
David Vilaseca’s autobiographical work, published in 2017 and adapted for the stage in 2022, problematizes the binary divisions between truth and fiction, success and failure, as well as some iterations within de dynamics between shame and pride. Through the analysis of some pertinent moments in Vilaseca’s work, this essay addresses several prevalent debates within Queer Studies in the last years, such as the explorations of the tensions around the notion of “shame” or the critical evaluation of the antisocial turn as well as the utopian vision within non-normative epistemologies. Furthermore, these pages aim to serve as a tribute of David Vilaseca, pioneer figure in the introduction of Queer Theories in Iberian (and Catalan) studies, and author of a monumental literary work that moves amidst the crevices of autobiography and fiction.
Keywords: Autobiography; Queer Theory; Catalan Literature; Theatre